Pengaruh Variasi Tinggi Bukaan Pintu Sorong Terhadap Bilangan Froude Dengan Material Pasir Sungai Dopi di Saluran Terbuka - Irnovia Berliana Pakpahan; Ni Made Linda; sri susilawati (Fakultas Teknik Universitas Tompotika Luwuk, 2026)
A sluice gate is a hydraulic control structure that functions to regulate flow discharge and water surface elevation in both the upstream and downstream sections of a hydraulic system. However, areas adjacent to the gate are highly susceptible to scour processes occurring both upstream and downstream of the structure. This study aims to analyze the effect of variations in sluice gate opening height on the Froude number in an open channel using Dopi River sand as the bed material. The research was conducted using an experimental laboratory approach in an open-channel flume. Three sluice gate opening heights (Yg) were investigated: 0.5 cm, 0.7 cm, and 1.0 cm, while maintaining a constant discharge (Q) of 226.231 cm³/s. The experimental results indicate that the sluice gate opening height significantly affects flow velocity. An inverse relationship was observed between gate opening height, flow velocity, and the downstream Froude number. As the gate opening decreases, the flow velocity increases, while the downstream water depth (y₁) becomes shallower. Furthermore, the gate opening height (Yg) influences the Froude number (Fr), where a smaller gate opening results in a higher downstream Froude number and greater scour depth due to the increase in flow velocity. The calculated Froude numbers downstream of the sluice gate for opening heights of 0.5 cm, 0.7 cm, and 1.0 cm were 0.261, 0.255, and 0.207, respectively. These values indicate that the flow regime remained subcritical (Fr < 1) under all tested conditions.